Objects as Communicative Mediators in Children With Autism Spectrum Disorder - Manzi, Federico; Savarese, Giulia; Mollo, Monica; Iannaccone, Antonio (Frontiers in Psychology, 2020)
In recent years, the socio-material perspective has informed an important interdisciplinary debate concerning the role of the physical world (i.e., the objects) in human psychological development. Several studies in the field of developmental psychology showed positive achievements in explaining the relationship between the subject and the social context through a socio-material approach, in particular in the early development. The importance of objects was also recognised in children with autism spectrum disorder (ASD), showing that these children are characterised by alterations in the use of the objects from early development. Some studies highlighted that objects could be a facilitator in the interactions between children with ASD and peers. However, the role of objects was not sufficiently investigated in interactions between children with ASD and adults. The main purpose of the present study was to investigate in children with ASD the communicative function that the activities with objects assume in the interactions with adults, highlighting the mediator role of objects in these interactions. More generally, this study also aims to highlight the relevance of adopting a socio-material perspective to highlight some neglected aspects of the psychological activity of children with ASD. To test this hypothesis, we conducted an extensive exploratory study, collecting data from a sample of three-year-old (N = 18; F = 3) and four-year-old (N = 26; F = 3) with ASD. Children were observed in a free-play situation with an adult. They were free to choose an object from a predefined set. Through quantitative data, we have described the general characteristics of the manipulation of objects; through qualitative data, we aimed to capture and describe, in microgenetic sequences, some characteristics of children's activities, defined as socio-material. The analysis of the socio-material activities suggested the role of objects as mediator of the interactions between children with ASD and adults.